2015
DOI: 10.1186/s12879-015-0993-x
|View full text |Cite
|
Sign up to set email alerts
|

Section’s osseous slice biopsy during major amputation of lower extremity: preliminary results of prospective cohort study

Abstract: BackgroundThe purpose of this cohort study was to assess the incidence of positive cultures in section’s osseous slice biopsy (SOB) taken at the level of major limb amputation. In case of positive cultures we sought whether the microorganisms present in SOB could take origin from the primary infection site necessitating the amputation. The impact of diabetes on culture results was also investigated.MethodsThis prospective cohort study, which aimed to confirm the results of the pilot study, analysed patients wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…12 Diabetic foot osteomyelitis silently spreads along the bone until it reaches a site of major limb amputation, in 45% of cases. 13 This suggests that there is a high probability of finding microorganisms in cultures from different areas of the same bone, regardless of being covered by healthy tissue. Under this assumption, the selection of PWB or TCB for the diagnosis of osteomyelitis would be irrelevant.…”
mentioning
confidence: 99%
“…12 Diabetic foot osteomyelitis silently spreads along the bone until it reaches a site of major limb amputation, in 45% of cases. 13 This suggests that there is a high probability of finding microorganisms in cultures from different areas of the same bone, regardless of being covered by healthy tissue. Under this assumption, the selection of PWB or TCB for the diagnosis of osteomyelitis would be irrelevant.…”
mentioning
confidence: 99%
“…In other words, surgery and medical parts of the management of DFO are linked by the results of bone specimen examination. This is true even in case of major amputations since several studies have shown that bone biopsies of the margins of the amputation are positive in a non-neglectable proportion of cases [4,5].…”
Section: Surgical Treatment Of Dfomentioning
confidence: 99%